HUBUNGAN DAYA TAHAN OTOT LENGAN DAN BAHU DENGAN HASIL 50 METER RENANG GAYA PUNGGUNG PADA CLUB BELIBIS KOTA PEKANBARU - Syafril Syaputra; Saripin '; Kristi August (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: Based on observation at Belibis swimming club Pekanbaru, the athletes’ ability of backstroke swimming is not optimalyed, as seen when they do backstroke swimming, a lot of athletes did’nt complete time target, because arm muscle fatigue. The aim of this study was to find out correlation of the endurance of arm muscles and shoulders with the result of 50 meters backstroke at Belibis club swimming Pekanbaru. The population in this study were all male athletes from Belibis Club Association Pekanbaru which consisted of 10 person. Sample by total sampling, therefore the total sample is 10 person. Instruments in this research was push-up and ability of 50 meters swim backstroke style. Obtained data were analyzed use product-moment correlation. Based on the result there is a significant relationship between endurance of arm muscles and shoulders with the result of 50 meters swim backstroke style at Belibis Club Pekanbaru, where rresult 0,677 > rtable 0,666. The value of coefficient correlation is in between 0,60 – 0,799, therefore the correlation is in the strong category.Keywords: Durability Of Arm Muscles and Shoulder, 50 Meters Backstroke Swimming